Central Bank Reserve Management and International Financial Stability-Some Post-Crisis Reflections - Jones, Bradley (IMF Working Papers; Working Paper ;, 2018)
Motivated by the tension first revealed during the global financial crisis between the domestic and international financial stability obligations of central bank reserve managers, this paper offers some reflections along four main lines. First, the paper highlights how official reserve management has evolved to mirror important aspects of private institutional investor behavior over time, and addresses the policy relevance of this convergence. Second, evidence is documented of procyclical portfolio behavior by reserve managers during the crisis, which added to the stabilization burden shouldered by central banks in reserve currency-issuing countries. Third, in appraising the evolution of related vulnerabilities since the crisis, the paper finds grounds for both cautious optimism and lingering concern, the balance of which points to an uncertain future resolution. Fourth, some potential remedies are presented to help dampen the procyclical impulses of reserve managers in future periods of international financial turbulence.